Martingales and Financial Mathematics - J.A.M. van der Weide (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2004)
In this expository paper, we will discuss the role played by martingales in Financial Mathematics. More precisely, we will restrict ourselves to a mathematical formulation of the economical concept of an arbitrage-free, complete market and the pricing of derivatives in such models. For a clear exposition, we only consider the discrete case. We also discuss the Cox-Ross-Rubinstein model which is still one of the most used models in Finance.